STRATEGI PENYALURAN ZIS DI LAZ ZAKAT SUKSES DALAM PENGENTASAN KEMISKINAN - Ilham Taufik Hidayat (2023)
The potential for zakat in Indonesia has a considerable value. Even so, zakat in Indonesia has not played such a role in community empowerment. This study focuses on the analysis of the ZIS fund distribution strategy carried out by the Amil Zakat Institution (LAZ) Zakat Sukses in poverty alleviation. Researchers will apply a combination of method triangulation techniques and data source triangulation. Thus, the validity of the information from each of these methods will be examined and provide concrete data results. This study also used the SWOT method, a combination of IFAS and EFAS. The results of this study provide an overview of the flow of Zakat, Infaq, and Sedekah (ZIS) in the Zakat Sukses LAZ which is divided into 2 ways, namely direct distribution as well as through the work program carried out and know the strategies performed through observations in the field, adjust the program to the problems of the community, involve mustahik in the program of distribution, and conduct an evaluation of the impact of the zakat researchers also give recommendations related to the ZIS distribution strategy that is more effective in reducing poverty based on the results of the SWOT matrix analysis.